1996
DOI: 10.1016/0304-3959(96)03137-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin antagonist bosentan blocks neurogenic inflammation, but is not effective in aborting migraine attacks

Abstract: Bosentan, a specific mixed antagonist of endothelin receptors with no vasoconstrictor activity, inhibits neurogenic plasma extravasation (NPE) within rat dura mater. This would predict efficacy in aborting migraine attacks, without causing cardiovascular side-effects. We investigated the efficacy of 250 mg i.v. bosentan in a randomized, double-blind, placebo-controlled, clinical trial. Improvement from moderate/severe to mild/no headache at 2 h (primary efficacy measure) occurred in 5/23 (22%) of bosentan-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 9 publications
0
48
0
3
Order By: Relevance
“…Redrawn from Saxena and Tfelt-Hansen (2006) trigeminal ganglion or systemic administration of capsaicin, has allowed studies on the activation of the trigeminal system and its effects on the cranial vasculature (for review, see Arulmani et al 2006). This review also contains data on the ability of several drugs to inhibit plasma protein extravasation (e.g., Weiss et al 2006), although it should be kept in mind that extravasation inhibitors, such as CP-122,288 (Roon et al 2000), the neurokinin-1 receptor antagonist lanepitant (Goldstein et al 2001a;Goldstein et al 1997), and the mixed ET A /ET B receptor antagonist bosentan (May et al 1996) proved ineffective in the treatment of migraine. Thus, the relevance of plasma protein extravasation in migraine is no longer tenable (Peroutka 2005).…”
Section: Receptor Subtypes Involved In Pharmacological Treatments Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Redrawn from Saxena and Tfelt-Hansen (2006) trigeminal ganglion or systemic administration of capsaicin, has allowed studies on the activation of the trigeminal system and its effects on the cranial vasculature (for review, see Arulmani et al 2006). This review also contains data on the ability of several drugs to inhibit plasma protein extravasation (e.g., Weiss et al 2006), although it should be kept in mind that extravasation inhibitors, such as CP-122,288 (Roon et al 2000), the neurokinin-1 receptor antagonist lanepitant (Goldstein et al 2001a;Goldstein et al 1997), and the mixed ET A /ET B receptor antagonist bosentan (May et al 1996) proved ineffective in the treatment of migraine. Thus, the relevance of plasma protein extravasation in migraine is no longer tenable (Peroutka 2005).…”
Section: Receptor Subtypes Involved In Pharmacological Treatments Of mentioning
confidence: 99%
“…In rats, ET-1 is one of the most potent inducers of Leão's spreading depression (Dreier et al 2002), but Goadsby et al (1996) reported no effect of endothelin receptor antagonists in preventing spreading depression in cats. The major setback for the hypothesis of involvement of ET-1 in migraine pathogenesis comes from a study showing the lack of efficacy of the mixed ET A /ET B receptor antagonist bosentan in migraine (May et al 1996). However, the ET A and ET B receptors are likely to mediate opposite effects, and it is feasible that more selective endothelin receptor antagonists may be effective in the acute treatment of migraine.…”
Section: Endothelin Receptorsmentioning
confidence: 99%
“…Consistent with this, the endothelin receptor antagonist, bosentan, which blocks neurogenic plasma extravasation in the dura mater [Brändli et al, 1996], was ineffective in aborting headache in migraine patients and may be attributable to its lack of vasoconstrictor activity [May et al, 1996]. Endothelins (ET-1 and -3) are potent vasoconstrictors.…”
Section: Cgrp Sp and Nka Involvement In Migrainementioning
confidence: 91%
“…Most of the evidence collected in patients indicates that drugs preventing neurogenic inflammation in animal models fail to be effective in migraine and that substances effective in migraine are relatively ineffective in the model of neurogenic extravasation. In fact, the endothelin antagonist bosentan blocks neurogenic inflammation, but is ineffective in aborting migraine attacks [11]. In addition, two substance P antagonists, RPR100893-201 and lanepitant (a neurokinin-1 antagonist), all potent inhibitors of neurogenic inflammation, were ineffective in acute migraine [12].…”
Section: Neuropeptide Receptor Antagonistsmentioning
confidence: 99%